PENGARUH KOMUNIKASI POLITIK TERHADAP PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN GUBERNUR SUMATERA UTARA TAHUN 2024 DI KOTA MEDAN - Ananta, Shintia; Pinem, Windawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of political communication on public political participation in the 2024 North Sumatra gubernatorial election. The problem in this study is the low political participation as seen from the high abstention rate of 41%. This I obtained from data at the KPU 024 Medan Tembung District, Indra Kasih Village. The novelty in this study is research that focuses on examining mediating or moderating factors that can influence the relationship between political communication and political participation. The research method used in this study is quantitative research. The number of samples is 40 people with a sampling technique using a random sampling technique. The data collection technique chosen is a questionnaire. The data analysis technique uses a simple linear regression analysis technique. Before conducting this test, prerequisite tests are carried out first, namely the normality test and the linearity test. Normality test Using the Liliefors test and getting results on political communication L0 = 0.137935284 and Ltable: 0.140089, then 0.137935284 < 0.140089 so that L0 < Ltable then the data on political communication is normally distributed. On political participation L0 = 0.134698739 and Ltable: 0.140089, then 0.134698739 <0.140089 so that L0 < Ltable then the data on political participation is normally distributed. Furthermore, the linearity test with the results of Fcount = 0.3489 and Ftable = 2.4123 so that Fcount <Ftable then H0 is rejected, meaning there is a linear relationship between political communication and political participation. Furthermore, the results of the simple linear regression test show the regression coefficient value for political communication (X) of 0.634436. This value is positive, meaning that political communication has a positive and directly proportional effect on political participation. Therefore, the higher the political communication, the higher the political participation. The correlation coefficient (r) and determination coefficient (r2) show the magnitude of the influence, as shown in the value r2 = 0.379456 = 37,95%. This indicates that the percentage contribution of political communication to political participation is 37,95%. While the remaining 62,05% is influenced by other factors. Therefore, it can be concluded that there is a significant and substantial influence on public political participation in the 2024 North Sumatra gubernatorial election in Medan City.